The influence of context, input and process aspects on assessment of science practical work achievement - Crispina Gregory K Han; Vincent Pang (Serial Publications Pvt.Ltd., 2016)
The purpose of this study was to examine the influence of context, input and process aspects on Assessment of Science Practical Work (ASPW) achievement among the form 4 students in Sabah. A total of 447 Form 4 students from all over Sabah were selected by using stratified sampling technique. Non-experimental quantitative research and survey method was used to collect data. Instruments used to collect data comprised Context Aspect Survey (CAS), Input Aspect Survey (IAS) and Process Aspect Survey (PAS), whereas result of ASPW was provided by the science Form 4 teachers who assessed the students using a standardized achievement indicator rubric provided by the Malaysian Examination Board. The Statistical Package for Social Sciences’ (SPSS) for Windows version 20.0, QUEST item analysis software, and Smart Partial Least Square (SmartPLS) version 2.0 software were used to analyze collected data. The findings showed that for the assessment of context, input and process aspect, the level of assessment was high (3.414.20) whereas the min of ASPW achievement according to the skills was at excellent level (8 or 9, Grade A). There was significant correlation and influence between context and input and between input and process. However, there was no significant correlation and influence between process and product. The result of paths analysis revealed that context, input and process aspects of ASPW do not correlate with the ASPW achievement. The findings of this study bring some implications especially the need to revise the process aspect, to ensure the input aspect fulfills the ASPW, and to consider other factors which are able to fulfill student’s requirement. Keyword: Assessment of Science Practical Work (ASPW), Context, Input and Process Aspects